Reformas al art. 18 de la ley notarial incorporando como potestad de la notaria o notario, la notificación al mandatario. - Jordan Ponce, Carmen Veronica (2015)
The Art. 18 of the Notarial Act provides for the powers of notaries, including several that were exclusive jurisdiction and now form part of the notarial field, such as the dissolution of the conjugal partnership, divorce by mutual consent requirement for compliance the promise of sale or obligations, however there are issues that have not yet been regulated for the benefit of the decongestion of the judiciary and remain the exclusive power of judges and judges. This is the case of notification to revocation of the power that is exclusive potestad of judges, ie must be done the deed of revocation of power before a notary or notary, then with that copy should sue the notification before a Judge or Judge of the Civil and Commercial Law, to issue a writ of acceptance for processing and arrange the summons to the person to whom the power is revoked and then said the person was revoked the power, you must have that marginalized in the Book of Protocol by the notary or notary where power is conferred. This could well be ignored for the person revoking the power notary notify the agent to know the will of the client to revoke the power of attorney and then marginalized in the book, with it, the citizen can do in one morning or maximum one day, while the judicial process in some cases must wait months to be served. As such, research has as its corollary the proposed amendment to Art. 18 of the Notarial Act which permitted the Notary notify the revocation of power to the president.